Efficient pairing-free CP-ABE based on ordered binary decision diagram - Sheng DING; Jin CAO; Hui LI (Tongxin xuebao)
To improve the computational efficiency of ABE,its access structure was optimized and a pairing-free CP-ABE scheme based on ordered binary decision diagram (OBDD) was proposed.Based on the elliptic curve cryptography,the complex bilinear pairing operation in traditional CP-ABE was replaced with the relatively lightweight scalar multiplication,thus the overall computation overhead was reduced.And OBDD was used as the access structure of CP-ABE,which can not only represent any Boolean expression about attributes,but also support both positive and negative attributes.The length of the key was independent of the number of attributes and the length of the ciphertext was only related to the number of valid paths in the access policy.The security and performance analysis show that the scheme can resist chosen plaintext attack under the decisional Diffie-Hellman (DDH) assumption,and the computation efficiency can meet the practical application requirements of Internet of things.